THE RURAL DEVELOPMENT AND RURAL SELF-SUFFIENCY IN BOGOR DISTRICT, WEST JAVA PROVINCE - Tri Budiarto; Ernan Rustiadi; Arya Hadi Dharmawan (TATALOKA, 2017)
This study aimed at map rural typologies based on the status of development and self-sufficiency of the rurals. Status of rural development was built with 11 indicators and status self-sufficient was built with six indicators. The study used secondary data from BPS, wich was PODES  2014 in 434 villages at Bogor district. Primary data was used to support the analysis results with field observations taken at four village representatives typology. The results showed that 187  villages were categorized as developed rurals and 247 villages as undeveloped rurals. Based on self-sufficient status, there were 78 villages categorized as self-sufficient rurals and 356 villages as unself-sufficient rurals. Based on the status of development and self-sufficient, three villages were categorized as typology I (developed and self-suffient rurals), 184 villages were typology II (developed and unself-suffient rurals), 172 villages were typology III (undeveloped and unself-sufficient rurals), and 75 villages were typology IV (undeveloped and self-sufficient rurals). Spearman correlation value was -0.371, there was an inverse relationship between the development status and self-sufficiency status of the rural